LEARNING FROM MISTAKES: STUDENTS’ PERCEPTION TOWARDS TEACHER'S ATTITUDE IN WRITING CORRECTION - Muliyah, Pipit; Rekha, Agnira; Aminatun, Dyah (Lexeme : Journal of Linguistics and Applied Linguistics, 2020)
Most of writing teachers agree that writing skill is the most difficult subject for foreign language learners. The difficulties come from complexity of planning, idea organization, revision, and the use of lexical and grammatical. Correcting or giving feedback to students? writing is also difficult for teachers, since it takes time and energy. Thus, this study tried to explore students? perception towards teachers? attitude in writing correction by distributing questionnaire to 20 students and 4 writing teachers, observing the teaching activities, and documenting students? work. The study showed the result that teachers and students responses revealed various discrepancies between teachers and students? perception for error and mistake correction. Then, most of students indicated that they do not understand the teachers? feedback towards their writing composition. Therefore, it is recommended that teachers incorporate classroom discussions on error correction, feedback, and writing in order to help their students understand how feedback is intended to affect their writing and why it is given in particular way.